Implementation of Content-Based Instruction Approach in Teaching English for Maritime at Vocational High School Pelayaran Buana Bahari - Muhammad Natsir; Bahagia Saragih (Randwick International of Education and Linguistics Science Journal, 2022)
This study aims to describe the implementation of the English for Maritime teaching method using the Content-Based Instruction approach at Vocational High School Pelayaran Buana Bahari, Medan. The subjects of this study were 30 students with a total of 10 students per class from grade ten, grade eleven, and grade twelfth. The data collected in the study was taken using a questionnaire containing questions about the implementation of the Content-Based Learning Approach in Teaching English for Maritime at Vocational High School Pelayaran Buana Bahari, Medan. The study was conducted once with data collection carried out for three days. From this study it can be concluded that the maritime English teaching method using the Content-Based Instruction Approach can improve students' competence in understanding English for Maritime because the teaching approach through this method is carried out in a structured and systematic manner so that the aim is to equip students with mastery of English for the benefit of marine communication can be achieved.